Loan management practices of local entrepreneur credit clients - Lorenzo, Maria Pilar M.
This study examine dthe loan management practices of micro-entrepreneur credit clients in terms of allocation and payment. The research also described the nature of loans, the reasons for loan application, the effects of the loans to micro-entrepreneurs and the loan-related problems encountered. A sample of fifteen micro-entrepreneur credit clients coming from two cooperatives was purposely chosen for the study. In-depth interviews were conducted to gather information-rich data from the entrepreneurs. The data were analyzed using descriptive statistics and content analysis. Results show that in general, the micro-entrepreneur credit clients do not understand the terms of their loans, which signifies the lack of cost and benefit assessment prior to loan acquisition. Furthermore, even though the loans are offered only for business expansion and development, the borrowers' intentions for loan application include personal and family-related reasons. Consequently, majority of the entrepreneurs use the loan for expenses that are unrelated to the business like household maintenance, family emergencies and children's education. The entrepreneurs make use of both proper and improper payment practices. Effective payment practices include the allotment of daily savings for loan payment and the utilization of the daily payment scheme to ease the burden of paying a large amount. On the other hand, the improper payment strategies utilized by the micro-entrepreneurs include using other sources of income and borrowing at a high interest pay for the loan.The perceived positive effect of loan acquisition to the entrepreneurs mainly concerns family-related benefits. Conversely, the negative effects of the loan consist of the anxiety caused by difficulties in paying the loans and the additional obligations imposed by the lending cooperatives. The usual problems that entrepreneurs experience include unforeseen events which inhibit loan payment and the policy of cooperatives requiring micro-entrepreneurs to pay for the arrears pf their partner-creditors. Generally, the micro-entrepreneurs have limited understanding of the nature of their loans. They also have misconceptions about the proper allocation and payment of the loans, which reflect their insufficient knowledge of loan management. Recommendations for credit organizations and home economics institutions, and future research are provided at the end of the paper.